Micronutrients Intake and Mathematics Achievement among Primary School Children in Magelang, Central Java - Arika, Romiza; Anantanyu, Sapja; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2020)
Background: Micronutrient deficiency in school children is estimated at more than 2 million children. Deficiency of micronutrients causes damage to the physical functioning of children, impaired cognitive function, learning processes that are less than optimal, and poor academic performance. This study aimed to analyze the relationships between iodine, iron, zinc intake, and math achievement primary school children.Subjects and Method: This was an observational analytic study with a cross sectional design. The study was conducted in four elementary schools in Pakis, Magelang, Central Java, from March to April 2019. A sample of 177 students was selected by simple random sampling. The dependent variable was math achievement. The independent variables were iodine, iron, and zinc intakes. The data were collected by questionnaire and analyzed by a multiple linear regression.Results: Iodine intake (b= 0.02; 95% CI= 0.01 to 0.03; p= 0.001) and zinc intake (b= 0.23; 95% CI= 0.04 to 0.41; p= 0.017), and iron intake (b= 0.08; 95% CI= -0.01 to 0.17; p= 0.052) increased math achievement in primary school children.Conclusion: Iodine intake, zinc intake, and iron intake increase math achievement in primary school children.Keywords: iodine, zinc, and iron, math achievement, primary school childrenCorrespondence: Romiza Arika. Masters Program in Nutrition, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: romizaarika652@gmail.com.Mobile: +6289506237763. Journal of Maternal and Child Health (2020), 5(2): 182-192https://doi.org/10.26911/thejmch.2020.05.02.08